Specification for flexible insulating sleeving. Specification requirements for individual types of sleeving. Heat-shrinkable polyolefin sleeving, general purpose, flame retarded, shrink ratio 2:1 Part 3-209, (17th June 2003) - British Standards Institution,
No abstract available